5 - Immigrant-Host Community Relations in Malawi’s Community Based Rural Land Development Project (CBRLDP) - Paul Kishindo, (African Sociological Review, 2016)
Access to land among land-poor households has always been contentious. In Malawi, the government, aware of this, started Community Based Rural Based Land Development Project (CBRLDP), financed by the World Bank. The project brought to the fore the latent antagonistic relationship between immigrants and host communities. This paper examines the antagonistic relationship that developed between one of the beneficiary groups of the project and their hosts in Chigumula village, Traditional Authority (TA) Liwonde’s area in Machinga district. Focus group discussion reveals that Resettlement of groups, whether sponsored or spontaneous, carries with it a potential for conflict with resident population arising from among other things competition for resources, status, power and dominance.